Refleksi Filosofi Pendidikan Multikultural dalam Membentuk Akhlakul Karimah Peserta Didik di SMPN 42 Bengkulu Utara - Irsal Irsal (UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: Good morals among students are still difficult to develop, it is seen that students still like to bully, tease, and find it difficult to appreciate diversity. The purpose of this study is to describe and analyze the reflection of the philosophy of multicultural education in forming the noble character of students at SMPN 42 Bengkulu Utara. Using a qualitative descriptive method with a library research approach. The results of the study show that reflection on multicultural education can form noble morals, because philosophically multicultural education is in line with the Islamic view that upholds the values of brotherhood, peace, and civility in life. The formation of noble morals through multicultural education that teaches the values of tolerance, justice, equality, mutual respect and mutual appreciation for diversity. Reflection on the philosophy of multicultural education seeks to carry out learning, self-development of students, and understanding in the learning process by instilling multicultural values, for personal and professional growth of students. So by reflecting on the experience of the multicultural education learning process, a person can learn, develop and become a better person with noble morals. Thus it can be concluded that multicultural education reflection can form students' noble morals. So it can be suggested to form students' noble morals then increase multicultural education reflection in schools.Keywords: Philosophical Reflection, Multicultural Education, Students' Morals. Abstrak: Akhlak karimah di kalangan peserta didik masih terasa sulit, terlihat peserta didik masih suka membuly, mengejek, sulit menghargai keberagaman. Tujuan penelitian untuk mendeskripsikan dan menganalisis refleksi filosofi pendidikan multikultural dalam membentuk akhlak karimah peserta didik di SMPN 42 Bengkulu Utara. Menggunakan metode kualitatif deskriftif pendekatan library research. Hasil penelitian menunjukan bahwa refleksi pendidikan multikultural dapat membentuk akhlak karimah, karena secara filosofis pendidikan multikultural sejalan dengan pandangan Islam yang menjunjung tinggi nilai persaudaraan, perdamaian, dan keadaban dalam kehidupan. Pembentukan akhlak karimah melalui pendidikan multikultural yang mengajarkan nilai-nilai toleransi, keadilan, kesetaraan, saling menghormati dan saling menghargai atas keberagaman. Refleksi filosofi pendidikan multikultural berupaya melakukan pembelajaran, pengembangan diri pseserta didik, dan pemahaman dalam proses pembelajaran dengan menanamkan nilai-nilai multicultural, untuk pertumbuhan pribadi, dan professional peserta didik. Sehingga dengan merefleksikan pengalaman dari proses pembelajaran pendidikan multikultural, maka seseorang dapat belajar, berkembang dan menjadi pribadi yang lebih baik dan berakhlak karimah. Dengan demikian dapat disimpulakn bahwa refleksi pendidikan multikultural dapat membentuk akhlak karimah peserta didik. Sehingga dapat disarankan untuk membentuk akhlak karimah peserta didik maka tingkatkan refleksi pendidikan multikultural di sekolah.Kata kunci: Refleksi Filosofis, Pendidikan Multikultural, Akhlakul Karimah Peserta Didik.